2019
DOI: 10.1038/s12276-019-0253-z
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen negatively regulates the renal epithelial sodium channel (ENaC) by promoting Derlin-1 expression and AMPK activation

Abstract: The main functions of the epithelial sodium channel (ENaC) in the kidney distal nephron are mediation of sodium and water balance and stabilization of blood pressure. Estrogen has important effects on sodium and water balance and on premenopausal blood pressure, but its role in the regulation of ENaC function is not fully understood. Female Sprague–Dawley rats were treated with 17β-estradiol for 6 weeks following bilateral ovariectomy. Plasma estrogen, aldosterone, creatinine, and electrolytes were analyzed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Arteriolar vasodilatation through 5-HT2 receptors inhibition [58][59][60] Antiepileptics Carbamazepine, 61 Baclofen 86 -increased capillary permeability especially with concomitant alcohol consumption 86 -GABAergic vasodilatation through central inhibition of sympathetic tone 87,88 -myogenic response inhibition through GABA A stimulation induced by loss of selectivity 89 Cytokines G-CSF, 90 interleukin 2, 91 interferon-α2b 36 Increased capillary permeability (as these drugs are responsible for capillary leak syndrome) Progestins 10 Sodium and water retention for progestins without anti-mineralocorticoid effect 106,107 Aromatase inhibitors: anastrozole, 108 letrozole, 108 exemestane 109 Sodium and water retention by removal of oestrogen-dependent ENaC receptors inhibition 110 SERM: tamoxifen 108,111 -sodium and water retention by removal of oestrogen-dependent ENaC receptors inhibition 110 -lymphedema through disturbance of lymphatic vasculature stability mediated by oestrogen receptors α 112…”
Section: Ceritinib Crizotinibmentioning
confidence: 99%
See 1 more Smart Citation
“…Arteriolar vasodilatation through 5-HT2 receptors inhibition [58][59][60] Antiepileptics Carbamazepine, 61 Baclofen 86 -increased capillary permeability especially with concomitant alcohol consumption 86 -GABAergic vasodilatation through central inhibition of sympathetic tone 87,88 -myogenic response inhibition through GABA A stimulation induced by loss of selectivity 89 Cytokines G-CSF, 90 interleukin 2, 91 interferon-α2b 36 Increased capillary permeability (as these drugs are responsible for capillary leak syndrome) Progestins 10 Sodium and water retention for progestins without anti-mineralocorticoid effect 106,107 Aromatase inhibitors: anastrozole, 108 letrozole, 108 exemestane 109 Sodium and water retention by removal of oestrogen-dependent ENaC receptors inhibition 110 SERM: tamoxifen 108,111 -sodium and water retention by removal of oestrogen-dependent ENaC receptors inhibition 110 -lymphedema through disturbance of lymphatic vasculature stability mediated by oestrogen receptors α 112…”
Section: Ceritinib Crizotinibmentioning
confidence: 99%
“…GnRH agonists: 108 gosereline, leuprolide Sodium and water retention by removal of oestrogen-dependent ENaC receptors inhibition 110 and through reduction of the antimineralocorticoid effect of progesterone 106,107 Antiandrogen: 99 abiraterone Sodium and water retention due to mineralocorticoid effect Anticortisolic: metapyrone 99 Sodium and water retention due to mineralocorticoid effect Insulin 113 -increased capillary permeability -arteriolar vasodilatation -sodium and water retention due to intrinsic antinatriuretic effect and through RAAS activation Growth hormone 114 Sodium and water retention through ENaC stimulation 115 Drugs for pulmonary arterial hypertension PGI 2 analogues/agonists: treprostinil, 116 selexipag 117 -increased capillary permeability -PGI 2 -dependent precapillary vasodilatation 118 Endothelin receptor antagonists: 119 ambrisentan, bosentan -precapillary arteriolar vasodilatation 119 -sodium and water retention through inhibition of natriuretic and aquaretic effects of ET B and ET A…”
Section: Ceritinib Crizotinibmentioning
confidence: 99%
“…For example, estrogen can provide nitric oxide or superoxide products according to the conditions of vascular walls [57]. The main function of the epithelial sodium channel (ENaC) in the kidney distal nephron, which mediates sodium and water balance and the stabilization of blood pressure, is affected by estrogen effects of increasing ubiquitination [58]. These seem to support the results of the heterogeneity test.…”
Section: Discussionmentioning
confidence: 61%
“…In our study, within the females, we found higher plasma creatine concentrations in females that were postmenopausal, as compared to premenopausal females. A potential explanation for the higher postmenopausal plasma creatine concentrations might be the fact that estrogens are able to activate AMP‐activated protein kinase (AMPK), which down‐regulates the creatine transporter in the proximal tubulus, leading to enhanced creatine excretion 51–53 …”
Section: Discussionmentioning
confidence: 99%